Membrane chloride transport measured using a chloride-sensitive fluorescent probe - Illsley, N P; Verkman, A S (Biochemistry (Easton), 1987)
Transport of chloride across cell membranes through exchange, cotransport, or conductive pathways is a subject of great biological importance. Current methods of measurement are restricted in their sensitivity, time resolution, and applicability. A new transport measurement technique has been developed on the basis of the fluorescence quenching by chloride of the dye 6-methoxy-N-(3-sulfopropyl)quinolinium (SPQ). SPQ fluorescence quenching by chloride is rapid (less than 1 ms) and sensitive, with a greater than 50% decrease in fluorescence at 10 mM chloride. SPQ fluorescence is not altered by other physiological anions or by pH and can be used to measure both neutral and conductive transport processes. The high water solubility and membrane permeability properties of SPQ make it ideal for use in both membrane vesicles and cells. Chloride transport determined with SPQ was validated by measurement of erythrocyte chloride/anion exchange and membrane vesicle chloride conductance.